2018
DOI: 10.24235/eltecho.v3i1.2911
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students’ Writing Skill Through Graphic Organizer in Process Writing

Abstract: Within a production of text like written text, a writer in fact conducts series of processes which are not simple and easy. Grammar, vocabulary and content are among the problems; however, problems actually occur begin from even deciding what to write and how the ideas should be arranged. Employing collaborative classroom action research (CAR) design in two cycles, three meetings of 100 minutes each, this study aims to improve the students' writing skill using graphic organizer. 16 students of an English cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…As such, the findings answer Research Question 1. These findings align with previous research conducted by several researchers, including Zainudin (2021), Selvaraj et al (2019), Yavani (2018), Servati (2012), Buzan (2009), and Novak et al (2008). According to their studies, Graphic Organisers have proven to be more effective than the Conventional Method in enhancing students' writing abilities.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As such, the findings answer Research Question 1. These findings align with previous research conducted by several researchers, including Zainudin (2021), Selvaraj et al (2019), Yavani (2018), Servati (2012), Buzan (2009), and Novak et al (2008). According to their studies, Graphic Organisers have proven to be more effective than the Conventional Method in enhancing students' writing abilities.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, students can improve their writing proficiency by building a network of ideas and identifying their relationships. Graphic Organisers also provide a practical learning approach that helps students link new knowledge to existing knowledge, draw conclusions, make assumptions, identify central ideas and supporting details, and summarise (Yavani, 2018). The application of Graphic Organisers has been successful in improving students' writing abilities (Selvaraj et al, 2019;Yavani, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The first study was conducted by Yavani (2018). Through Classroom Action Research, he revealed that the majority of EFL learners were able to foster their academic writing skills through graphic organizers successfully since the learners will be more familiar with the process of metacognitive strategies in terms of planning, drafting, revising, and designing the final writing products.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is a Classroom Action Research (CAR) which was conducted by Yavani (2013) who tried to solve the writing problem of the writing class of Elementary 4 level at Lembaga Bahasa dan Pendidikan Professional (LBPP) LIA Malang through the implementation of graphic organizer in writing persuasive article. The subjects of the research are the twenty people of adult learners whose age are between 20 to 30 years old who study English Writing in level Elementary 4.…”
Section: Introductionmentioning
confidence: 99%